Digital Payments and Their Impact on The Indian Economy - Agarwal, Abhishek (Global journal of Business and Integral Security, 2024)
The Indian economy has witnessed a significant transformation over the past few years, driven in part by the rapid adoption of digital payments. This paper aims to provide a comprehensive analysis of the impact of digital payments on various aspects of the Indian economy. The paper begins by providing an overview of the digital payments landscape in India, highlighting the key players and trends. It then examines the impact of digital payments on financial inclusion, and consumer behavior. The paper also discusses the challenges and opportunities associated with the adoption of digital payments in India. Finally, the paper concludes with policy recommendations to promote the further growth and adoption of digital payments in the country.